Successful management of a neonate with antenatally detected mature intrapericardial teratoma - Annie Arvind; Ramasamy Rajeshkumar; Deepak Thakur; Anuradha Sridhar; Muthukumaran Chinnasamy Sivaprakasm (Wolters Kluwer Medknow Publications, 2019)
Intrapericardial teratoma is a germ-cell tumor that typically arises from the base of the heart and usually diagnosed in the fetal or neonatal period. Although benign, these tumors can be massive in size causing direct compression of the heart. Life-threatening complications such as fetal hydrops, cardiac failure, superior vena cava syndrome, and cardiac tamponade caused by these teratomas have been reported. Early surgical excision is curative. We present the images of a mature intrapericardial teratoma diagnosed in an asymptomatic neonate. The neonate was managed successfully by elective surgical excision.